Implementation of Remedial Programs to Achieve Learning Completeness in Islamic Religious Education Learning: A Literature Review - Mubarakatun Nikmah; Zumratul Azka; Suwadi Suwadi (FKIP - Universitas Riau, 2026)
Remedial programs in Islamic Religious Education (PAI) learning are needed to help students who have difficulty understanding Islamic concepts, which has an impact on low academic achievement. Many students have not reached the Minimum Completeness Criteria (KKM) in the cognitive, affective, and psychomotor domains. However, the implementation of remedial measures is often constrained by time constraints, lack of resources, and low student motivation to learn. This study aims to analyze the implementation of remedial programs in improving student learning completeness in PAI subjects. The method used is qualitative with a literature study approach, while content analysis is used to examine various academic sources related to challenges and remedial success factors. The results of the study showed that remedial programs contributed positively to improving learning outcomes and strengthening students' religious values. Effective strategies include identifying individual needs, applying contextual learning methods, personalized approaches to teaching, and continuous evaluation. However, various obstacles are still faced, such as limited teacher skills and low student motivation. Recommended solutions include strengthening collaboration between teachers, schools, and parents, as well as professional training for educators. With systematic planning and consistent implementation, remedial programs can realize fairer, more inclusive, and comprehensive PAI learning.